2022
DOI: 10.3389/fimmu.2022.846281
|View full text |Cite
|
Sign up to set email alerts
|

CD90 Marks a Mesenchymal Program in Human Thymic Epithelial Cells In Vitro and In Vivo

Abstract: Thymic epithelium is critical for the structural integrity of the thymus and for T cell development. Within the fully formed thymus, large numbers of hematopoietic cells shape the thymic epithelium into a scaffold-like structure which bears little similarity to classical epithelial layers, such as those observed in the skin, intestine or pancreas. Here, we show that human thymic epithelial cells (TECs) possess an epithelial identity that also incorporates the expression of mesenchymal cell associated genes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In distinction to previous methods that often include multiple myeloid growth factors, such as interleukin (IL) 1, IL3, IL6, granulocyte-macrophage colony stimulating factor (GM-CSF), and tissue necrosis factor ( Lyadova et al., 2021 ), we found that using M-CSF as the sole myeloid factor was sufficient to efficiently induce functional macrophages from the endothelial cell stage onward, and it maintained hPSC-macrophages over a prolonged period of in vitro culture ( Figure S2 ). An optimized version of the basal medium free of albumin also enabled the derivation of endodermal cell lineages from hPSCs and primary human tissue ( Sun et al., 2022 ), potentially facilitating co-culture studies. Our streamlined differentiation protocol efficiently generated macrophages that resembled those created with more complex methods (as reviewed in Lyadova et al., 2021 ), forming a robust platform upon which to undertake functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…In distinction to previous methods that often include multiple myeloid growth factors, such as interleukin (IL) 1, IL3, IL6, granulocyte-macrophage colony stimulating factor (GM-CSF), and tissue necrosis factor ( Lyadova et al., 2021 ), we found that using M-CSF as the sole myeloid factor was sufficient to efficiently induce functional macrophages from the endothelial cell stage onward, and it maintained hPSC-macrophages over a prolonged period of in vitro culture ( Figure S2 ). An optimized version of the basal medium free of albumin also enabled the derivation of endodermal cell lineages from hPSCs and primary human tissue ( Sun et al., 2022 ), potentially facilitating co-culture studies. Our streamlined differentiation protocol efficiently generated macrophages that resembled those created with more complex methods (as reviewed in Lyadova et al., 2021 ), forming a robust platform upon which to undertake functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thymic regeneration is an effective way to restore the body's adaptive immune system in order to rebuild an extensive library of T cells (Figure 2). 215,216 Cochlea mainly has the functions of sound transmission and sensory function. More and more people suffer from sensorineural hearing loss (SNHL) due to the aging of the population, long-term exposure to noise, genetics, diseases, drugs, trauma, and other factors.…”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%
“…Thymic regeneration is an effective way to restore the body’s adaptive immune system in order to rebuild an extensive library of T cells (Figure ). , Tajima et al decellularized the thymus by freeze–thaw cycles and scale. Studies have shown that decellularized thymic scaffolds can effectively promote the homing of bone marrow-derived lymphocyte progenitor cells and support the development of multiple functional T cells …”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%
“…The thymus is the main lymphoid organ and is composed of thymic cells and thymic stromal cells. Thymic stromal cells include thymic epithelial cells (TECs), fibroblasts, dendritic cells and endothelial cells [ 1 , 2 ]. TECs are composed of cortical TECs (cTECs) and medullary TECs (mTECs).…”
Section: Introductionmentioning
confidence: 99%